EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA - Wahyuni Wahyuni (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concept is one of basic skills that must be developed in according to the purpose of learning. However, the reality at school shows that students' understanding of mathematical concepts is still low. Cooperative learning model type TAI can be used as a solution. The purpose of this research is to compare students’ understanding of mathematical concepts who learn with cooperative learning model type TAI and conventional approach. This type of research is a quasi experiment with static group design. The instruments is tests of understanding of mathematical concepts. Based on data analysis concluded that cooperative learning model type TAI gives positive influences to the student’s understanding of mathematical concepts in class VIII SMP Negeri 22 Padang.Keywords – Understanding of mathematical concept, Cooperative Learning, Team Assisted Individualization (TAI)